2015
DOI: 10.1007/s11938-015-0050-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment to Improve Acute Kidney Injury in Cirrhosis

Abstract: Acute kidney injury (AKI) is an ominous complication of decompensated cirrhosis, which can be fatal if not treated promptly. It is important that clinicians recognize that AKI has occurred and institute timely treatment. Recent establishment of diagnostic criteria and treatment guidelines are most useful, and these will be further refined as treatments are being modified to improve patient outcome. To manage such a patient, firstly, the cause of the AKI needs to be identified and any precipitating factors corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…More recently, the KDIGO criteria have been developed to reach a consensus drawing consolidating elements of both RIFLE and AKIN on staging AKI [15]. Whether these criteria improve the traditional criterion (a final threshold value for sCr of 1.5mg/dl) in terms of a better prediction of mortality is still a matter of debate [16]. Piano et al reported that the traditional criterion was more accurate than the AKIN criteria in the prediction of in-hospital mortality in patients with cirrhosis and ascites [17].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the KDIGO criteria have been developed to reach a consensus drawing consolidating elements of both RIFLE and AKIN on staging AKI [15]. Whether these criteria improve the traditional criterion (a final threshold value for sCr of 1.5mg/dl) in terms of a better prediction of mortality is still a matter of debate [16]. Piano et al reported that the traditional criterion was more accurate than the AKIN criteria in the prediction of in-hospital mortality in patients with cirrhosis and ascites [17].…”
Section: Discussionmentioning
confidence: 99%
“…22 Midodrine has resulted in similar positive outcomes in other cohorts with hepatorenal syndrome. [25][26][27]…”
Section: Cirrhosis With Ascitesmentioning
confidence: 99%